Crystal structure of TiBi(2) - Watanabe, Kei (International Union of Crystallography, 2016)

(untitled) (Acta Crystallogr E Crystallogr Commun)
Black granular single crystals of monotitanium dibismuth, TiBi(2), were synthesized by slow cooling of a mixture of Bi and Ti from 693 K. The title compound is isostructural with CuMg(2) (orthorhombic Fddd symmetry). Ti atoms are located in square antiprisms of Bi atoms. The network of one type of Bi atom spirals along the a-axis direction while honeycomb layers of the other type of Bi atom spreading in the ab plane interlace one another.